Profile of tezacaftor/ivacaftor combination and its potential in the treatment of cystic fibrosis - Shiferaw D; Faruqi S (Dove Medical Press, 2019)
Dejene Shiferaw,* Shoaib Faruqi*Department of Respiratory Medicine, Hull University Teaching Hospitals NHS Trust, Cottingham HU16 5JQ, UK *These authors contributed equally to this workCorrespondence: Shoaib FaruqiDepartment of Respiratory Medicine, University of Hull and Hull and York Medical School, Hull University Teaching Hospitals NHS Trust, Castle Hill Hospital, Castle Road, Cottingham HU16 5JQ, UKTel +44 148 262 6706Email Shoaib.Faruqi@hey.nhs.ukAbstract: Cystic fibrosis (CF) is a life-limiting autosomal recessive disease caused by dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) ion channel. Management of CF has traditionally relied upon managing complications of CFTR protein dysfunction and this has led to a steady improvement in survival of CF patients. However, the landscape of CF care has changed substantially over the last decade with the discovery of CFTR modulators that aim to increase or potentially restore the function of the disease-causing CFTR protein. This narrative review summarizes the development of CFTR therapies so far with emphasis on tezacaftor/ivacaftor combination therapy. We have also summarized the Phase II results of triple combination therapy which promises an effective CFTR modulator therapy for more than 90% of CF patients.Keywords: cystic fibrosis, CFTR modulators, CFTR potentiators, ivacaftor, tezacaftor, triple therapy